Frailty among Older Adults Who Developed Acute Coronary Syndrome during Hospitalization for Noncardiac Illness and Their Outcome: A Prospective Observational Study - Arun David; Priya Vijayakumar; M Vijayakumar (Journal of the Practice of Cardiovascular Sciences)
Background: Atypical presentations of acute coronary syndrome (ACS) delay its recognition and treatment in older adults. During hospitalization, functional decline and delirium which are common to elder patients, lead to prolonged hospitalization, frailty, and poor clinical outcome. Steps taken for its prevention are usually not considered the top priority by the cardiologist. The present study was conducted to identify frailty among older adults who developed ACS during hospitalization for noncardiac illness and their outcome. Materials and Methods: Three hundred and ten older adults with ACS were included from June 26, 2020, to October 13, 2020. Subjects were divided into those admitted primarily due to an ACS (Group I, n = 94) and those developing ACS following admission for noncardiac illness (Group II, n = 216). Comorbidities, medications, investigations, management, outcome, and clinical frailty scale were compared between the two groups at the time of admission, after 30 days, and after 6 months. Results: Majority of them had non-ST elevation ACS (90.2%) in Group II, and acute kidney injury (27.1%) was the most common reason for admission. Optimum management was given to a lesser extent due to the current clinical condition of these patients. Frailty and physical disability during hospitalization and follow-up were more in Group II. Conclusion: Clinicians must be vigilant for the development of frailty when an older adult is admitted to the hospital, as early detection and optimum management provide better clinical and functional outcomes.